A cross-sectional study of severe acute malnutrition impact on auditory evoked potentials in children age 6–59 months - Anju Agarwal; Virendra Verma; Prachi Arya; Neetu Sharma; Ajit Singh Rajput (Asian Journal of Medical Sciences, 2023)
Background: Malnutrition is a public health concern in India. According to NFHS-5, the number of children under 5 years who are stunted (less height-for-age) and underweight (less weight-for-age) in India, are 35.5% and 32.1%, respectively. Many researchers reported that malnutrition affects myelination and neural maturation of the auditory brainstem pathway. Aims and Objectives: In this study, auditory evoked potential (AEP) parameters were studied in severly acute malnutrition (SAM) children of 6 months to <5 years of age. Materials and Methods: Fifty children, with severely malnourished (Their weighted age was 51–60% of the expected weight, and height for age <85% of the expected height) and 50 healthy children (with weight >80% of expected with normal height for their age), aged 6–59 months were included in the study. The parameters of AEPs were recorded using RMS-EMG EP MARK II, a 4-channel machine. Results: In our study, 30 (60%) males and 20 (40%) females had severe acute malnutrition. There were significant differences in the mean latencies of the waves I to V and the mean interpeak latencies (IPLs) of the waves I-III and I-V on the right and left ears between the study and control groups (P<0.05). The mean IPLs of I-III and I-V on the right side were found to be longer in the SAM group than in the control group (P<0.05. While the mean absolute peak latencies of wave, I found prolonged on both ears in the children with SAM (P<0.05). Conclusion: In the present study, severely acute malnourished children showed changes in AEPs characterized by absolute wave prolonged latencies and interpeak intervals compared with normally nourished children.